The deregulation of urban transport. Background and application of the neoliberal project in passenger transport in Santiago de Chile, 1974 - 1983 - Castillo Fernández, Simón; Vila Muga, Waldo Claudio (Universidad Academia de Humanismo Cristiano, 2023)
The deregulation of collective transport was carried out by the Chilean dictatorship progressively from 1974 to 1983, concluding with the complete freedom of routes, frequencies and rates. This process promoted a new framework for surface transportation, turning the little and middle entrepreneurs into a monopoly actor, obeying the neoliberal turn of the regime. It is argued that this transition implied that the State delegated several of its historical functions to the gremio del rodado, in a highly sensitive service for the population, delivering the organization of the various transportation media to the market. We use official sources, technical reports and the press, in order to reconstruct in an exploratory manner the origin of a controversial public policy, projected until the beginning of 1990.